The Development of a 3D Tai Dam Alphabet Models Using Augmented Reality Technology to Enhance Tai Dam Language Learning Achievement for the Tai Dam Community in Chiang Khan District, Loei Province - Jaruteerapan, Phatnutsooda (Journal of Information and Learning [JIL], 2024)
This research aims 1) to create a 3D model of the Tai Dam alphabet using augmented reality technology of the Tai Dam community, Chiang Khan District, Loei Province, 2) to study the academic achievement of the 3D model of Tai Dam alphabet using augmented reality technology, and 3) to evaluate user satisfaction towards 3D model of Tai Dam alphabet presented through augmented reality technology. The sample groups used in this study consisted of children aged 7-12 years and teenagers aged 13-20 years in the Tai Dam community, Chiang Khan District, Loei Province, totaling 48 people. The research tools were a 3D model of Tai Dam language alphabet in augmented reality totaling 39 letters, a 3D model quality assessment form, a test to measure academic achievement in a 3D model of Tai Dam alphabet before and after use, and a satisfaction assessment form with a 3D model of Tai Dam alphabet. The statistics used to analyze the data were mean, standard deviation, and one-group hypothesis testing (t-test dependent). The results showed that 1) creating a 3D model of Tai Dam language alphabet used through the AR Tai Dam language alphabet application had a file size 176 of megabytes and allowed users to see images as virtual objects in the real environment in 3D format. The results of the quality assessment of the 3D model of Tai Dam alphabet were overall at the highest level (M = 4.75, SD = 0.31). 2) The academic achievement of students after learning with 3D model of Tai Dam alphabet was significantly higher than before learning at the .05 level. 3) The satisfaction results of student with learning by the 3D model of Tai Dam alphabet were overall at a high level. (M = 4.46, SD = 0.14).